EXPLORING LANGUAGE AND ETHNIC IDENTITY AMONG INDONESIAN GENERATION Z - Ira Maria Fran Lumbanbatu (Indonesian EFL Journal, 2024)
Since Indonesia consists of hundreds of local languages, exposed to globalization and technological development, all of these make Generation Z face the complex situation of multiple languages. This complex situation encourages the generation Z to decide which language should be prioritized in their daily activities. Because of this situation, this study aims to explore what languages are used by Generation Z and what are the language attitude or perception of this generation created especially for local language and connect with their perception about the language related to cultural identity. A survey-based approach is used to examine the language attitude and perception by Generation Z towards their local language in Indonesia. This study used random sampling method in selecting the participants. It can reach 202 participants of Generation Z at Universitas Negeri Malang, East Java. In collecting the data, survey and in-depth interview are using in this study. The finding are most participants use Indonesia, English and their local language in their daily conversation. Related to language use by Generation Z, it can be also found that Javanese participants have the higher percentage in using the local language compare with the non-Javanese participants. It is also shown that mostly the participants do not agree that the ability in using local language is a determinant of the ethnic identity. Other factors should be considered for this case, for example how the participants practicing the ethnicity, understanding the history of the culture and contributing in the cultural activities.